Case Report: Misdiagnosis of Maturity-Onset Diabetes of the Young as type 1, type 2 or gestational diabetes: insights from a Latin American tertiary center - Ruiz-Urbaez, Rossana; Males-Maldonado, David; Villagómez-Estrada, Mariela Viviana; Reyes-Silva, Carlos; Salazar-Vega, Jorge; Jaramillo-Koupermann, Gabriela; Sosa-Copa, Diana; Gea-Izquierdo, Enrique (Frontiers in Medicine, 2025)
BackgroundMaturity-Onset Diabetes of the Young (MODY) comprises monogenic, non-syndromic forms of diabetes inherited in an autosomal dominant pattern. MODY is frequently misdiagnosed as type 1 diabetes (T1D), type 2 diabetes (T2D), or gestational diabetes mellitus (GDM). Studies suggest that 50–90% of MODY cases are erroneously classified as type 1 or type 2 diabetes, and up to 5% of women with GDM may have undiagnosed MODY. However, data regarding the clinical presentation and genetic characterization of MODY in Latin American populations remain scarce. This study aimed to describe the clinical, analytical, and genetic characteristics of MODY patients initially misdiagnosed as T1D, T2D, or GDM in a Latin American tertiary care center.MethodsMedical history, clinical and laboratory data were obtained from electronic medical records to assess diagnostic accuracy and identify phenotypic patterns suggestive of MODY. Whole exome sequencing (WES) was employed to detect mutations related to monogenic variants.ResultsWe identified five patients with MODY. The median age at diabetes diagnosis was 13.6 years, while the median age at MODY diagnosis was 25.8 years. The average duration between the initial diabetes diagnosis and confirmation of MODY was 12.2 years. None of the patients presented with diabetic ketoacidosis at the onset of diabetes. All patients tested negative for islet cell autoimmunity. Of the five patients, two were initially misclassified as having T1D, two as T2D, and one as GDM. Whole-exome sequencing (WES) identified a pathogenic missense variant, c.94G>A (p.Gly32Ser), in the INS gene (MODY10) in one patient initially diagnosed with T1D. Another patient, also misclassified as T1D, carried a pathogenic missense variant, c.709A>G (p.Asn237Asp), in the HNF1A gene (MODY3). Additionally, two patients initially diagnosed as T2D were found to carry missense variants: a likely pathogenic variant, c.613G>T (p.Asp205Tyr) in the GCK gene (MODY2) and pathogenic variant, c.4135C>T (p.Arg1379Cys) in the ABCC8 gene (MODY12), respectively. The patient initially diagnosed with GDM was revealed to have a pathogenic frameshift variant, c.616dupC (p.His206Profs*38), in the NEUROD1 gene (MODY6). Based on these findings, a change in therapeutic approach was implemented.ConclusionsMODY is often misdiagnosed, leading to delays in appropriate management. Whole-exome sequencing is crucial for identifying pathogenic variants, enabling accurate reclassification and tailored therapy.